2003
DOI: 10.1039/b211268j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photophysical properties of new two-photon absorption chromophores containing a diacetylene moiety as the central π-bridge

Abstract: We report two-photon absorption properties of newly synthesized compounds consisting of styrylpyridines or their triflates linked by a diacetylene p-bridge in a symmetric way as well as the compounds containing the same substituent groups linked by a phenylenevinylene-type p-bridge. Femtosecond open aperture Z-scan measurements revealed that the two-photon absorption cross-sections s (2) of the diacetylene compounds in DMSO were in the order of 10 248 cm 4 s molecule 21 photon 21 in the wavelength range of 650… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
61
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 43 publications
3
61
0
Order By: Relevance
“…In the quest of improving NLO properties, attention has been essentially focused on dipolar molecules for several decades. [1][2][3] More recently, quadrupolar systems have been designed and investigated [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and have shown improved properties, in particular with respect to the trade-off between optical transparency and NLO performance. Lately, attention has turned toward multipolar [22][23][24][25][26][27][28][29][30][31][32][33] and branched structures including dendrimers.…”
Section: Introductionmentioning
confidence: 99%
“…In the quest of improving NLO properties, attention has been essentially focused on dipolar molecules for several decades. [1][2][3] More recently, quadrupolar systems have been designed and investigated [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and have shown improved properties, in particular with respect to the trade-off between optical transparency and NLO performance. Lately, attention has turned toward multipolar [22][23][24][25][26][27][28][29][30][31][32][33] and branched structures including dendrimers.…”
Section: Introductionmentioning
confidence: 99%
“…Usually double bonds, due to their simple synthetic accessibility, are used in the backbone of the PIs to extend the conjugation length although the so obtained r TPA is normally lower than that of the triple-bondcontaining counterparts. 19,20 However, double bonds tend to attenuate the desired photochemical processes by cis-trans isomerization.…”
mentioning
confidence: 99%
“…In comparison to the phosphonate (2), the phospholipid phosphatide (3) possesses the advantages of low stereo-hindrance effect and high flexibility [13], which increased its reaction ability with aldehyde groups. The results indicated that the obtained average molecular weight by Wittig-Horner reaction was greatly improved (from M n =2087 in Wittig reaction to M n =10690 in Wittig-Horner reaction).…”
Section: Resultsmentioning
confidence: 99%